The protein corona effect for targeted drug delivery. Issue 1 (1st March 2013) - Caracciolo, Giulio
Abstract : At present, ligand binding to nanoparticle surface is the most widespread strategy for targeting specific tissues by a receptor-mediated mechanism. However, the nanoparticles are immediately covered by a protein-rich layer when administrated in vivo, the so-called "protein corona", with the immediate consequence that the ligand-receptor recognition may be obscured. It is not the nanoparticle-bulk composition or surface functionalization but rather the identity, arrangement and residence time of the proteins of the corona that determine the nanoparticle bioidentity, and this is an emerging concept available for use to target specific cell types in a controlled manner. An in-depth understanding of the relationship between surface properties of nanoparticles and composition of the "protein corona" is a fundamental step toward the design of nanoparticles that, once in the blood, become covered by specific proteins able to deliver them at the right site of action and promote efficient cell internalization. This "protein corona effect" is a formidable challenge that could lead to a complete renewal of the current strategies of targeted drug delivery. At present, ligand binding to nanoparticle surface is the most widespread strategy for targeting specifi c tissues by a receptormediated mechanism. However, the nanoparticles are immediately covered by a protein-rich layer when administrated in vivo, the so-called "protein corona", with the immediate consequence that the ligand-receptor recognition may be obscured. It is not the nanoparticle-bulk composition or surface functionalization but rather the identity, arrangement and residence time of the proteins of the corona that determine the nanoparticle bioidentity, and this is an emerging concept available for use to target specifi c cell types in a controlled manner. An in-depth understanding of the relationship between surface properties of nanoparticles and composition of the "protein corona" is a fundamental step toward the design of nanoparticles that, once in the blood, become covered by specifi c proteins able to deliver them at the right site of action and promote effi cient cell internalization. This "protein corona effect" is a formidable challenge that could lead to a complete renewal of the current strategies of targeted drug delivery.